Categorizing Two Taiwanese Major Political Parties From Their Faces: The Influence of Provincial Appearance - Chien-Kai Chang; Chien-Kai Chang; Mary Wen-Reng Ho; Sarina Hui-Lin Chien; Sarina Hui-Lin Chien (Frontiers in Psychology, 2018)
People go beyond the inferences afforded by a person’s observable features to make guesses about personality traits or even social memberships such as political affiliations. The present study extended Hu et al. (2016) to further investigate the influence of provincial appearance on differentiating KMT (Kuomintang) and DPP (Democratic Progressive Party) candidates by headshot photos with three experiments. In Experiment 1 (Membership categorization task), participants categorized the photos from the pilot study (where the difference between the perceived age of KMT and DPP candidates was reduced) and divided into four blocks by their perceived age. We found that participants were able to distinguish KMT from DPP candidates significantly better than chance, even when the perceived age difference between the two parties was minimized. In Experiment 2 (Trait rating task), we asked young and middle-aged adults to rate six traits on candidate’s photos. We found that “provincial appearance” is the core trait differentiating the two parties for both young and older participants, while “facial maturity” is another trait for older participants only. In Experiment 3 (Double categorization task), we asked participants to categorize the photos from the Exp. 1 on their membership (KMT or DPP) and on provincial appearance (mainlander or native Taiwanese) in two separate sessions. Results showed that young adults were likely to use the “provincial appearance” as the main characteristic cue to categorize candidates’ political membership. In sum, our study showed that Taiwanese adults could categorize the two parties by their headshot photos when age cue was eliminated. Moreover, provincial appearance was the most critical trait for differentiating between KMT and DPP candidates, which may reflect a piece of significant history during the development of the two parties.